2001
DOI: 10.1021/ie0007062
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Screening for the Supercritical Hydrogenation of Polyunsaturated Hydrocarbons Using VLE Calculations

Abstract: Preliminary knowledge of VLE behavior of multiphasic reaction mixtures is required for the operation and design of chemical reactors that work with supercritical fluid as solvents. In this case, the operating parameters of a continuous fixed-bed catalytic reactor are to be optimized for the selective hydrogenation of 1,5,9-cyclododecatriene (CDT) to form the second intermediate cyclododecene (CDE). Commercial simulators (Aspen, HYSYS, PRO-II), as well as a user-written program based on high-pressure flash calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…To avoid this limitation, a supercritical solvent that brings the substrate phase and the gas into a homogeneous single phase has been introduced. For soluble fatty acid derivatives, lower alkanes could be used, propane being the preferred one. Consequently, in recent years, some studies have reported the hydrogenation of oleochemicals at supercritical single-phase conditions. Indeed, a large number of chemical reactions have been successfully conducted in supercritical fluids.…”
Section: 13 Fatty Alcoholsmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid this limitation, a supercritical solvent that brings the substrate phase and the gas into a homogeneous single phase has been introduced. For soluble fatty acid derivatives, lower alkanes could be used, propane being the preferred one. Consequently, in recent years, some studies have reported the hydrogenation of oleochemicals at supercritical single-phase conditions. Indeed, a large number of chemical reactions have been successfully conducted in supercritical fluids.…”
Section: 13 Fatty Alcoholsmentioning
confidence: 99%
“…For soluble fatty acid derivatives, lower alkanes could be used, propane being the preferred one. [943][944][945] Consequently, in recent years, some studies have reported the hydrogenation of oleochemicals at supercritical single-phase conditions. Indeed, a large number of chemical reactions have been successfully conducted in supercritical fluids.…”
Section: Fatty Alcoholsmentioning
confidence: 99%
“…Hydrogen and nitrogen are anti-solvents in CO 2 solution, 17,18 meaning that they decrease the solubility of other solutes. To illustrate the anti-solvent effect of H 2 , we used the Peng-Robinson equation of state to calculate the change in solubility of naphthalene in scCO 2 at 40 °C.…”
Section: Anti-solvent Effect Of H 2 On Catalyst Solubilitymentioning
confidence: 99%
“…Furthermore, the methanol synthesis reaction is highly exothermic, posing a potential runaway hazard [15]. Therefore, investigations for substitutes of CO 2 , with emphasis on lower alkanes (ethane to hexane), are currently underway [16,17].…”
Section: Introductionmentioning
confidence: 99%